Effect of palpable vs. impalpable cricothyroid membranes in a simulated emergency front‐of‐neck access scenario. (19th January 2018) - Pairaudeau, C. F.; Mendonca, C.; Hillermann, C.; Qazi, I.; Baker, P. A.; Hodgson, R. E.; Radhakrishna, S.
Summary: The Difficult Airway Society 2015 guidelines recommend and describe in detail a surgical cricothyroidotomy technique for the can't intubate, can't oxygenate (CICO) scenario, but this can be technically challenging for anaesthetists with no surgical training. Following a structured training session, 104 anaesthetists took part individually in a simulated can't intubate, can't oxygenate event using simulation and airway models to evaluate how well they could perform these front‐of‐neck access techniques. Main outcomes measures were: ability to correctly perform the technical steps; procedural time; and success rate. Outcomes were compared between palpable and impalpable cricothyroid membrane scenarios. Anaesthetists' technical abilities were good, as assessed by a video analysis checklist score. Mean (SD) procedural time was 44 (16) s and 65 (17) s for the palpable and impalpable cricothyroid membrane models, respectively (p ≤ 0.001). First‐pass tracheal tube placement was obtained in 103 out of the 104 palpable cricothyroidotomies and in 101 out of the 104 impalpable cricothyroidotomies (p = 0.31). We conclude that anaesthetists can be trained to perform surgical front‐of‐neck access to an acceptable level of competence and speed when assessed using a simulator.